2020
DOI: 10.3892/etm.2020.8622
|View full text |Cite
|
Sign up to set email alerts
|

CDR1as/miR‑7/CKAP4 axis contributes to the pathogenesis of abdominal aortic aneurysm by regulating the proliferation and apoptosis of primary vascular smooth muscle cells

Abstract: Abdominal aortic aneurysm (AAA) is characterized as dilation of the aortic wall. Dysregulation of vascular smooth muscle cells (VSMCs) can contribute to the development of this phenotype. Circular RNAs and microRNAs (miRNAs) can regulate the proliferation and apoptosis of VSMCs. This present study aimed to identify the mechanisms of action behind the regulation of cerebellar degeneration-related protein 1 antisense RNA (CDR1as)/miRNA (miR)-7 in VSMCs. The expression levels of miR-7 were upregulated, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Studies have revealed that circRNAs principally bind to miRNAs to act as RNA sponges and increase downstream gene expression by inhibiting miRNA activities, thus contributing to disease progression ( Song et al, 2020 ; Wang et al, 2016 ; Zhao, Chen & Jiang, 2020 ). Similarly, for circHIPK3, the most classical mechanism for its functional effect is to act as a sponge for miRNAs, blocking the binding of miRNAs with downstream target genes and regulating the expression of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that circRNAs principally bind to miRNAs to act as RNA sponges and increase downstream gene expression by inhibiting miRNA activities, thus contributing to disease progression ( Song et al, 2020 ; Wang et al, 2016 ; Zhao, Chen & Jiang, 2020 ). Similarly, for circHIPK3, the most classical mechanism for its functional effect is to act as a sponge for miRNAs, blocking the binding of miRNAs with downstream target genes and regulating the expression of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…circ_0020397 plays an important role in the phenotypic modulation of intracranial aneurysms by promoting VSMC viability via the miR-502-5p/GREM1 axis ( 56 ). Additionally, CDR1as serves as a sponge for miR-7, which increases the expression of CKAP4 to facilitate the proliferation and suppress the apoptosis of VSMCs, leading to VSMC remodeling and progression of abdominal aortic aneurysm (AAA) ( 57 ). circCBFB facilitates VSMC proliferation and inhibits VSMC apoptosis via the circCBFB/miR-28-5p/GRIA4/LYPD3 axis ( 58 ).…”
Section: Circrna As Cerna In Cvdsmentioning
confidence: 99%
“…There are over 70 miR-7 binding sites in the cerebellar degeneration-related protein 1 antisense RNA (CDR1as), and these sites regulate the effect of CDR1as on the target gene expression [ 93 ]. According to recent research, the expression levels of CDR1as and CKAP4 (the estimated miR-7 target) are lower in AAA cases than those in normal controls [ 94 ]. Zhao et al suggested that the CDR1as/miR-7/CKAP4 axis plays a role in VSMCs of AAA cases and that CDR1as upregulation may curb the expression of miR-7.…”
Section: Verified Circrnas In Aaasmentioning
confidence: 99%